On PWM Strategies and Current THD for Single- and Three-Phase Cascade H-Bridge Inverters with Non-Equal DC Sources - Akhmetov, Zhansen; Hammami, Manel; Grandi, Gabriele; Ruderman, Alex (MDPI, 2019)
Cascade H-bridge (CHB) inverter is an attractive choice for integration of DC sources of different nature, e.g., for distributed generation with energy storage, photovoltaic generation, etc. In general, non-equal DC voltage sources can affect the total harmonic distortion (THD) of the CHB by introducing undesirable low-frequency subharmonics. This paper investigates different level-shifted (LS) and phase-shifted (PS) pulse width modulation (PWM) strategies for single- and three-phase cascade H-bridge inverters with non-equal DC sources from the load current THD minimization perspective. The best current quality is provided by LS PWM, as reported in the literature. The paper provides a simple time domain explanation of LS PWM superiority. However, PS PWM may be a preferable choice for practical applications due to fair power and loss sharing across individual H-bridges. The paper explains how to obtain the best current quality by PS PWM carriers’ order arrangement (DC sources switching sequence selection).
Keywords: multilevel inverters; total harmonic distortion; level-shifted PWM; phase-shifted PWM